Efficiency and equity: The Swedish economy in comparison to other countries at the beginning of the 21st century - Bogusław Czarny; Elżbieta Czarny (International Journal of Management and Economics, 2021)
Referring to economic ideals of efficiency and equity, we are comparing the state of the Swedish economy in the early 21st century to the situation in other countries, especially the other Nordic countries, the United States (US), and Poland. After presenting the basic facts about Nordic countries we examine the issue of economic efficiency. In addition to gross domestic product (GDP) we use the Human Development Index (HDI), the findings of the economics of happiness, and the number of registered triadic patent families as measures of efficiency. Then we analyze the issue of equity. We use the Gini coefficient, the extent of poverty, the level of unemployment, and the level of intergenerational mobility of earnings as measures of equity. The analysis reveals that inhabitants of Sweden and the other Nordic countries have been achieving some of the best economic results in the world. This applies to the level of GDP per capita in these countries, to the capability of inhabitants to utilize their full potential, and to their life satisfaction. These countries' ability to create innovation is impressive. At the same time, Nordics have successfully reduced the scale of social inequalities and ensured relatively equal opportunities for all citizens. This is evidenced by low income inequality, low unemployment, and low poverty rate in these countries. Sweden and the other Nordic countries are superior to the US both in terms of efficiency and equity. Poland, on the other hand, lags far behind Nordics, as well as the US, in terms of efficiency, as exemplified by the relatively low GDP per capita and very low innovation in Poland. In terms of equity, however, Poland loses to Nordics but seems to win to the US.
Keywords: P52; 650; comparative economic systems; Nordic model; Sweden